Boundary element methods for axisymmetric heat conduction and thermoelastic deformations in nonhomogeneous solids - Yun, Bao Ing (2013)
This thesis is concerned with the development of boundary element techniques for the numerical solution of several important classes of axisymmetric heat conduction and thermoelastic problems involving nonhomogeneous solids with material properties that vary continuously in space. The problems under consideration have applications in the analyses of functionally graded materials which play an important role in engineering.